African and Native American foodways and resilience - Lindsey Lunsford; Melvin Arthur; Christine Porter (Journal of Agriculture, Food Systems, and Community Development, 2021)
The COVID-19 pandemic is flooding and splitting “efficiency” fault lines in today’s industrialized food system. It also exploits centuries of historical traumas, White supremacy, and systemic racism to kill non-White people at triple the rates of Whites.